Towards a Global Regime of Higher Education - Do, Paolo (Praktyka Teoretyczna, 2015)
This paper rethinks the spatialization of educational institutions at the global level, scaling and rescaling the space of the university as an inclusive process that makes academic knowledge production something heterogeneous, complex and composite, and proposing a regime for the higher education system based on a stratified relationship that is asymmetrical and geographically displaced. Moreover it outlines the “new” political economy of knowledge, which is a particular mechanism in contemporary capitalist production, capable of creating an artificial scarcity of knowledge by means of hierarchies, and reproducing the classical law of value in a regime based on abundance instead of scarcity.